2010
DOI: 10.1002/hbm.20927
|View full text |Cite
|
Sign up to set email alerts
|

Power calculations for multicenter imaging studies controlled by the false discovery rate

Abstract: Magnetic resonance imaging (MRI) is widely used in brain imaging research (neuroimaging) to explore structural and functional changes across dispersed neural networks visible only via multisubject experiments. Multicenter investigations are an effective way to increase recruitment rates. This article describes image-based power calculations for a two-group, cross-sectional design specified by the mean effect size and its standard error, sample size, false discovery rate (FDR), and size of the network (i.e., pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Moreover, underpowered studies are difficult to justify ethically. Maps of within-center variance derived from calibration experiments of the type described here are suitable for power calculations that predict key parameters of trial design [Suckling et al, , 2010. Furthermore, choice of acquisition protocol or data processing pipeline can be made based on outcomes of the power calculations.…”
Section: Relationship To Other Calibration Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, underpowered studies are difficult to justify ethically. Maps of within-center variance derived from calibration experiments of the type described here are suitable for power calculations that predict key parameters of trial design [Suckling et al, , 2010. Furthermore, choice of acquisition protocol or data processing pipeline can be made based on outcomes of the power calculations.…”
Section: Relationship To Other Calibration Experimentsmentioning
confidence: 99%
“…Furthermore, choice of acquisition protocol or data processing pipeline can be made based on outcomes of the power calculations. By making these calculations on a voxelwise basis, the predictions are also adaptable to specific neurobiological hypotheses that may include regions with a range of within-center variances that in turn impact on organisational decisions [Suckling et al, 2010].…”
Section: Relationship To Other Calibration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…So multicenter datasets are needed. Recent data sharing projects such as the 1000 Functional Connectomes Project (Biswal et al, 2010), the International Neuroimaging Data-sharing Initiative (INDI) (Mennes et al, 2013) and the Autism Brain Imaging Data Exchange (ABIDE) (Di Martino et al, 2014) have revealed that resting-state fMRI datasets obtained from multi-sites are fruitfully aggregated for discovery and replication (Tomasi and Volkow, 2012) and is regarded that analysis using multi-center data can facilitate recruitment, increase study power, and overcome between-scanner variance to produced more generalizable results revealing common regions that contribute to classification consistently within each dataset (Biswal et al, 2010;Gradin et al, 2010;Moorhead et al, 2009;Suckling et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have evaluated the effects of using different scanners and/or scanner upgrade on morphometric results [11,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Regarding volumetric measurements, there is generally greater inter-scanner variability than intra-scanner variability.…”
Section: Discussionmentioning
confidence: 96%